2010
DOI: 10.1177/0192623310378136
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer and Environmental Chemical Exposure: A Review of Our Current State of Knowledge With Reference to the Role of Hormones and Hormone Receptors as an Increased Risk Factor for Developing Lung Cancer in Man

Abstract: Lung cancer is a dominant cause of cancer mortality. The etiology of lung cancer is mainly related to cigarette smoking, airborne genotoxic carcinogens, and arsenic, but its sex-specific incidence suggests that other mechanisms, such as hormones, may also be involved in the process of carcinogenesis. A number of agents commonly present in the living environment can have dual biological effects: not only are they genotoxic / carcinogenic, but they are also hormonally active as xenoestrogens. This dualism may ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 90 publications
0
22
0
1
Order By: Relevance
“…In fact, regulations on pollutants should take into account new scientific evidences on age and gender differential susceptibilities [105,106].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, regulations on pollutants should take into account new scientific evidences on age and gender differential susceptibilities [105,106].…”
Section: Resultsmentioning
confidence: 99%
“…Substances with estrogenic actiivity may promote neoplastic changes in specific tissues, as in case of breast and lung cancer [18][19][20][21]; the case of another major cancer, colorectal cancer, is more difficult. Colon epithelium is rich of ERbeta receptors and an estrogenic action may significantly increase the cancer metastic potency [22]; however, the impacts, whether protective or adverse, of estrogen and estrogen-acrtive substances on cancer promotion are still matter of discussion [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, exposure to environmental-chemical carcinogens are other associated risk factors (3). The mechanism of lung tumorigenesis is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…These inflammatory mediators may further promote neoplasia by inducing preneoplastic mutation, proliferation, resistance to apoptosis, invasiveness, angiogenesis, and secretion of immune suppressive factors [3]. Aside from the tumorigenic effects of NNK alone, emerging data suggested that other environmental toxicants are also considered to play significant roles in the development of lung cancer [4]. 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) is a member of the polyhalogenated aromatic hydrocarbon family and is one of the most toxic environmental compounds produced by industrial combustion and chemical manufacturing processes [5].…”
Section: Introductionmentioning
confidence: 99%